Davao Milk Processing Plant (DMPP) - Reyes, Mie Shen B. (School of Management, University of the Philippines Mindanao, 2009)
Davao Milk Processing Plant (DMPP) is a local milk producer and processor operating at Malagos, Calinan, Davao City. It has established its name in the local market with the Davao Dairy Best brand name since 1990. In 2005, a new owner and management took over the plant?s operation in the hope of maximizing its capacity. With a new vision and mission and the desire to forge a better future for the stakeholders of the plant, the management of Davao Milk Processing Plant took on the challenge of developing a strategic plan for the plant?s entire operation in the next five years (5) years. Adopting an Agribusiness System for Davao Milk Processing Plant, a study was done on the current situation of the plant?s entire operation and the Philippine Dairy Industry through research and personal interviews with the dairy farmers, plant employees, and concerned government agencies. Representatives of every subsystem from the suppliers of the factors of production to the end-consumers were considered in developing the entire agribusiness system of DMPP. The Quantitative Strategic Planning Matrix (QSPM) was used as a tool in selecting the best strategy for DMPP. Based on the QSPM, the recommended core strategy for DMPP is to improve its entire agribusiness system focusing on the key strategic dimensions: sufficient supply of raw materials, quality and productivity, innovation capabilities, and efficient consumer response. The result is a Strategic Plan for Davao Milk Processing Plant that clearly states its vision, mission, strategic priorities, sustainability policy, and the required program (including its key result areas) to fulfill them.